2D Animation on Being New Parent - Pratama, Jimmy; Kelvin, Kelvin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The transition to parenthood is a multidimensional challenge that often causes emotional and practical stress for new parents, particularly in understanding proper infant care. This study aims to address these issues by developing a 2D animated educational video titled